Exosomes in Pathogenesis, Diagnosis, and Treatment of Hepatocellular Carcinoma - Li, Shuang; Chen, Limin (Frontiers in Oncology, 2022)
Exosomes are extracellular vesicles with a diameter of 30-150 nm that are released by most types of cells and have been confirmed to be involved in many physical and pathological processes, especially in cell to cell communication. Compared with other vesicles, exosomes have a unique double-layer saclike structure that allows them to be present stably in various body fluids, including blood, cerebrospinal fluid, urine, saliva, and serous cavity effusion. The cargoes of exosomes reflect the characteristics of host cells. Due to the nature of hepatocellular carcinoma (HCC) cells, heterogeneity in the bioactive substances usually exist in exosomes. In addition, exosomes can efficiently deliver cargoes to the target cells to exert pathological functions, playing important role in tumor occurrence, development, metastasis, immune regulation, and drug resistance. Previous studies have been shown that exosomes have wide applications in diagnosis and treatment of HCC. In this review, we discuss these recent findings and highlight the significant roles of exosomes in HCC, focusing on the effect and underlying mechanisms of exosomes to regulate HCC progression and the potential clinical value of exosomes as biomarkers and therapeutic targets.